Liberation of Life (Itinera, 2015)
Philosophy and music can achieve the same thing by different means. This paper considers three types of improvisation (on a harmonic structure [jazz], free, and “deep listening”) as steps in an investigation on freedom in musical improvisation, as well as on its potential liberation of life. As an alternative to the well-known concepts of “rapid” or “instant composing”, here musical improvisation is conceived of as the production of a present – in which life is present to itself – through composition-for-improvisation and as a kind of poetic work designed to give one a “voice” of one’s own.